The Relationship between Particulate Matter and Length of Exposure to Respiratory Complaints and Lung Function Disorder among Brick Craftsmen in Aceh Besar - Dianova, Sri; Febriansyah, TM.; Yanti, Budi; Andayani, Novita; Yusuf, Nurrahmah; Kurniawan, Ferry Dwi; Salawati, Liza (Indonesian Society of Respirology (ISR), 2024)
Background: Brick craftsmen are heavily exposed to particulate matter (PM) from brick burning, possibly contributing to respiratory complaints. The research aims to evaluate the association between PM levels, duration of exposure, respiratory complaints, and lung function disorders among brick craftsmen in Aceh Besar. Method: The research method is observational analytic with a cross-sectional design. It was conducted in September 2023 on 68 respondents to assess lung function using spirometry and PM levels using the Air Quality Monitor. Results: The data analysis revealed restrictive types of lung function disorders (47.1%), 75% of participants had worked for more than three years with working hours ≥8 hours/day (100%), the most frequent respiratory complaint was coughing (23.5%) and shortness of breath (13.2%), and the dominant type of work was brick molding (67.6%) rather than burning (32.4%). The PM2.5 index in the brick manufacturing area is classified as very dangerous (100%), while the PM10 index is identified as very unsafe (55.6%) and very dangerous (44.4%). The correlation analysis revealed a significant connection between PM2.5 as well as PM10 and lung function impairments (values of P=0.002 and 0.012, respectively). There was a significant correlation between work periods and lung function impairments (P=0.037). Multivariate analysis showed that a working term of 1-3 years was strongly linked with lung function disorder (FEV1) among brick craftsmen in Aceh Besar (P=0.026). Conclusion: This study showed that PM exposure was significantly associated with impaired lung function but not with respiratory complaints. Furthermore, a long working period is significantly associated with respiratory symptoms, especially for workers with 1-3 years, and is associated with impaired lung function in brick artisans in Aceh Besar.